L2 motivation research 2005–2014: Understanding a publication surge and a changing landscape. (December 2015) - Boo, Zann; Dörnyei, Zoltán; Ryan, Stephen
Abstract: The study of L2 motivation has seen an unprecedented boom during the past decade, with the number of published studies in the area far exceeding not only the amount of work done in other domains of language learner characteristics but, in fact, most strands within the whole of SLA research. This study examines the origins and nature of this extraordinary surge by reviewing a large dataset of journal articles and book chapters published between 2005 and 2014 (N = 416) in terms of the broad quantitative patterns they display with respect to theoretical and research methodological trends. The results (a) provide insights on the changing landscape of the field and (b) allow for projections to be made about the directions in which the field is headed.